Efficiency of public R&D management agency and its improvement toward open innovation - Byung Yong Hwang; Sung-Hun Park; Dae-Cheol Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
R&D management agencies have been taking on key roles in the national R&D ecosystem. The purpose of this study is to suggest ways to improve the role of R&D management agencies for R&D planning and evaluation. It analyzed the regulatory system and relative efficiency of the current use of planning and evaluation cost. Data-collection sources included documents, surveys, and interviews with staff members in agencies responsible for national R&D management. By using DEA models, relative efficiency was measured. Based on the analysis results, we present suggestions for improvement in three areas: (a) establishment of institutional basis; (b) improvement of budget process; (c) improvement measures depending on the causes of inefficiency. Finally, future directions and the limits of this study are discussed.
Keywords: 650; Data Envelopment Analysis; National Innovation System; open innovation; public R&D management agency; R&D performance